Comparative corrosion behavior of Zn with Fe and Mg in the course of immersion degradation in phosphate buffered saline. (October 2016) - Chen, Yingqi; Zhang, Wentai; Maitz, Manfred F.; Chen, Meiyun; Zhang, Heng; Mao, Jinlong; Zhao, Yuancong; Huang, Nan; Wan, Guojiang
Graphical abstract: Highlights: Corrosion behavior of Zn with Fe and Mg in immersion degradation course acquired. The transient electrochemical corrosion results of Zn lie between Fe and Mg. Nonetheless, Zn corroded faster than Fe and Mg in long-term immersion degradation. Such degradation profile is due to localized corrosion mode and products changing. Distinction must be drawn between its transient assay and long-term results. Abstract: The corrosion behavior of Zn was compared with those of Fe and Mg in a long-term course of immersing in phosphate buffered saline (PBS) as biodegradable metal for bio-implants application. The comparison focused on corrosion rate, mode, products and surface characteristics along the immersion degradation up to 21 days. For transient assays, the open circuit potential and corrosion rate placed Zn between Fe and Mg. However, in a long-term course the corrosion rate of Zinc developed faster than Fe and Mg. This was ascribed to its unique localized corrosion and corrosion products changing in contrast to Fe and Mg.